Frontiers in thoracic oncology: new breakthroughs in molecular targets and immunotherapy - Yang, Yujing; Pu, Dan; Li, Xuehan (Frontiers in Immunology, 2025)
Thoracic tumors, including lung cancer, breast cancer, and thymoma, usually present poor outcomes. The current treatment methods for thoracic tumors have low efficacy and are associated with severe adverse reactions. Molecular targeted therapy and immunotherapy offer new possibilities for the treatment of thoracic tumors. In this review, we have summarized the latest research on these novel therapeutic strategies, and discussed their clinical applications, challenges, and possible countermeasures. This review offers a theoretical basis for improving the outcomes of thoracic tumor patients, along with future research prospects.